Heinrich Himmler's Cultural Commissions : Programmed Plunder in Italy and Yugoslavia - Dow, James R. (Book collections on Project MUSE., 2018)
German scholars were early pioneers in folklore and historical linguistics. As the Nazis rose to power, however, these disciplines were distorted into racist pseudoscience. Under the direction of Heinrich Himmler's SS-Ahnenerbe (Ancestral Inheritance), folklore became a tool for constructing a unified German realm and a manufactured lineage from ancient and "pure" Germanic and Nordic blood. Drawing on extensive research in public and private archives and interviews with family members of fieldworkers, James R. Dow uncovers both details of the SS cultural commissions' work and the continuing vestiges of the materials they assembled. Teams of poorly qualified and ideologically motivated collectors were sent to South Tyrol in Italy and Gottschee in Slovenian Yugoslavia, from which ethnically German communities were to be resettled in the German Reich. Although a mass of information on narratives, songs and dances, beliefs, customs, local clothing and architecture, and folk speech was collected, the research was deeply tainted and skewed by racialist and nationalist preconditions. Dow sharply critiques the continued use of these ersatz archives